Global Method Application Deret Dadu Alfabet Media Assisted in Efforts to Improve Reading Ability Beginning (Research on Class II Students SD Negeri Sikepan 2) - Hafidzotunnissa’, Husna (Prosiding University Research Colloquium, 2021)
This study aims to determine the improvement of pre-reading skills through the global method assisted by Deret Dadu Alfabet media in grade II students of SD Negeri Sikepan 2. This study used Classroom Action Research (CAR) held in grade II SD Negeri Sikepan 2 apply three cycles. Each Each cycle is followed by four stage, namely: (1) planning action, (2) implementation of actions, (3) action observation and (4) action reflection. The subjects of this study were all grade II students of SD Negeri Sikepan 2 totaling 12 student with 8 male student and 4 female student. Methods of data collection in this study using a performance test sheet, pretest and posttest question, and observation sheet. Methods of data analysis in this study using quantitative data and qualitative data. The result of this research shows there is an increase in the activity of grade II students from 42% to 83%, and an increase in the average initial reading ability of students from 63 to 88 with a mastery percentage of 42% to 83%, and each cycle is increasing. Based on the result of this study, it can be concluded that the global method assisted by Deret Dadu Alfabet media is effective in